PELATIHAN PEMBUATAN MASKER CLAY PADA NNB DI DESA SIALOGO KECAMATAN ANGKOLA BARAT: PELATIHAN PEMBUATAN MASKER CLAY PADA NNB DI DESA SIALOGO KECAMATAN ANGKOLA BARAT - elmi, Hasibuan elmi; Ulma Sintia; Dini Mayasari; Susi Yanti; Yulia Vera; Afrinadewi Lubis; Mhd E Arsyad Rambe (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2024)
Dry skin occurs when the skin lacks moisture. One practical solution to overcome this problem is to use a clay mask formulated with carrot extract and rice flour. This research aims to develop a clay mask containing carrot extract and rice flour. Carrot extract is rich in beta-carotene which functions to protect the skin from exposure to UV rays, and contains vitamin A and antioxidants which help brighten the skin. Aging in general is a natural process that no one can put down. The carotenoid content in carrots can be seen from the intensity of the color, namely the more orange the color of the carrot, the more carotenoid it contains. Almost everyone wants to have perfect facial skin, especially young women. Teenagers, especially young women, are familiar with skincare.